Proposing Solutions to the Problems of Water Users for the Services Provided by the Water Supply State Enterprise in Luang Prabang Province (Case Study: Luang Prabang City) - DUANGCHAMPA, Kathi; INTHAPANYA , Sangkhom; CHANSAVANG , Bounsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of the research is: 1) To study the level of problems of water users regarding the service provided of the Water Supply State Enterprise in Luang Prabang City; 2) Proposals to solution the problem for the service of the Water Supply State Enterprise in Luang Prabang City in the future. which uses study methods by using questionnaires and interviews to collect data from a sample group of 64 areas of type 1 residential water users within the Luang Prabang City in a total of 390 households and then bring the data to quantitative analysis using Program SPSS Version 2025 into analysis. The results of the study of the level of problems of water users to the services of the State Water Corporation in Prabang in terms of repair services, public relations information, water registration and collection services, water pressure and water quality as a whole are few problems with an average value of 2.08 and Proposing a solution to the problem of water users in relation to the service provided by the Water Supply State Enterprise in Luang Prabang City is to improve the water pressure, repair services to quickly adapt to the conditions, have enough water in the dry season to continue as usual, provide information to the public including public relations and other services with a total of only 35.90% of all proposals.